Subinternship in Radiology – A Practical Start to the Specialization? - Kasch, R.; Wirkner, J.; Hosten, N.; Hinz, P.; Napp, M.; Kessler, R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: To identify factors influencing medical students to choose radiology in the four-month clinical elective in the final year of medical school following radiology subinternships.Materials and Methods: A subsample of medical students in a nationwide German online survey evaluated a subinternship in radiology (19 items). They were divided into four groups: Students who could imagine doing a clinical elective in radiology in the practical year based on their experiences during the subinternship (“yes, based on subinternship”), students who could not (“no, based on subinternship”) and students who had made this decision prior to the subinternship (“yes, prior to subinternship” and “no, prior to subinternship”).Results: 94 medical students evaluated a radiology subinternship (54.4 % females). Based on their experiences during the subinternship, 54 students (57.4 %) intended to do a final year clinical elective in radiology, 39 of them (41.5 %) being encouraged by the subinternship. 40 (42.6 %) reported having a negative attitude towards a clinical elective in radiology, 16 of them (17.0 %) having made this decision based on their subinternship experience. Groups did not differ regarding gender (p = 0.396) and age (p = 0.853). Students motivated to do a final year clinical elective in radiology experienced excellent academic teaching (p = 0.001) and practical involvement (p = 0.003), achieved their learning goals more often (p = 0.001), were better integrated into the team (p = 0.001), and acquired more practical skills (p = 0.003). Overall satisfaction was higher in these groups (p = 0.001).Conclusion: Satisfaction with a radiology subinternship is crucial for motivating medical students to do a final year clinical elective in radiology. A structured subinternship and continuous mentoring should be targeted to keep students connected to radiology.Key Points:• Radiology subinternships influence further interest in the specialization.• The quality and structure of teaching critically influence student satisfaction.• Team integration and practical involvement positively affect the attitude towards a specialization.Citation Format:• Kasch R, Wirkner J, Hosten N et al. Subinternship in Radiology – A Practical Start to the Specialization? Fortschr Röntgenstr 2016; 188: 1024 – 1030
Keywords: medical students; future career choices; work satisfaction; subinternship radiology